Cultural Differences in Attitudes towards Therapy and Help-Seeking Behavior in Sweden - Dahlberg, Elsa (International Journal of Psychology, 2024)
Purpose: The aim of the study was to analyze the cultural differences in attitudes towards therapy and help-seeking behavior in Sweden. Methodology: This study adopted a desk methodology. A desk study research design is commonly known as secondary data collection. This is basically collecting data from existing resources preferably because of its low cost advantage as compared to a field research. Our current study looked into already published studies and reports as the data was easily accessed through online journals and libraries. Findings: In Sweden, cultural differences impact attitudes towards therapy and help-seeking behavior. While therapy acceptance is rising among Swedes, those from collectivist cultures often view it negatively due to mental health stigma. Conversely, individuals from individualistic cultures are more open to therapy. This highlights the necessity for culturally sensitive mental health services and targeted interventions to address barriers to help-seeking behavior. Unique Contribution to Theory, Practice and Policy: Individualism-collectivism theory, cognitive-behavioral theory & social identity theory may be used to anchor future studies on the cultural differences in attitudes towards therapy and help-seeking behavior in Sweden. Mental health professionals should develop and implement culturally tailored interventions that address the unique attitudes towards therapy and help-seeking behavior prevalent in Sweden. Policymakers should prioritize initiatives that increase diversity and cultural competence within the mental health workforce in Sweden.